KEDUDUKAN HUKUM SENTANA ABUT KELADI DALAM HUKUM ADAT BALI, IMPLIKASINYA TERHADAP HAK WARIS DAN MEKANISME PENYELESAIAN KONFLIK - Ni Luh Sukma Imagy; Komang Arya Mukti Maruti; Ni Luh Made Elida Rani (FAKULTAS ILMU AGAMA DAN KEBUDAYAAN, 2025)
This study examines the mechanism of adoption known as sentana abut keladi in Balinese customary law and its legal implications for the status of the adopted couple or child, including its impact on inheritance rights and customary obligations. The research employs a normative legal research method, using a conceptual approach and a statutory approach to analyze relevant customary norms and legal principles. The sentana abut keladi process is conducted to ensure the continuity of lineage, social responsibility, and spiritual obligations within the family. This process involves family consent, formal recognition by the desa adat (customary village), and the performance of the peperasan ceremony, which serves as a valid customary ritual to legitimize the adoption. Upon completion of these customary procedures, the adopted parties whether a husband, wife, or couple acquire a legal status equivalent to that of biological children, including full inheritance rights and customary duties within the adoptive family. However, the practice of sentana abut keladi may give rise to inheritance disputes, particularly when competing family interests emerge or when tensions arise between traditional patrilineal principles and modern notions of legal equality. The resolution of such inheritance disputes requires an integrated approach between Balinese customary law and national civil law. In this context, the desa adat plays a central role as mediator and interpreter of customary norms, while judges function as arbiters who balance customary law with national legal principles. This integrated dispute resolution mechanism aims to ensure social, legal, and spiritual justice while maintaining harmony within Balinese customary communities.